Solving the puzzle of subhalo spins - Wang, Yang; Lin, Weipeng; Pearce, Frazer R.; Lux, Hanni; Muldrew, Stuart I.; Onions, Julian (American Astronomical Society, 2015)
Investigating the spin parameter distribution of subhalos in two high-resolution isolated halo simulations, recent work by Onions et al. suggested that typical subhalo spins are consistently lower than the spin distribution found for field halos. To further examine this puzzle, we have analyzed simulations of a cosmological volume with sufficient resolution to resolve a significant subhalo population. We confirm the result of Onions et al. and show that the typical spin of a subhalo decreases with decreasing mass and increasing proximity to the host halo center. We interpret this as the growing influence of tidal stripping in removing the outer layers, and hence the higher angular momentum particles, of the subhalos as they move within the host potential. Investigating the redshift dependence of this effect, we find that the typical subhalo spin is smaller with decreasing redshift. This indicates a temporal evolution, as expected in the tidal stripping scenario.